Dėl keleto retesnių liaudinių vaivorykštės pavadinimų - Buivydienė, Rūta (Baltistica, 2006)
ON SEVERAL RARE FOLK TERMS FOR ‘RAINBOW’ (LITH. vaivórykštė)The article deals with several rare folk names for ‘rainbow’ in the Lithuanian language: vaivóraikštė, vaivórakštė, vovẽrykščia, stangà, žebeñkštė, sverblė̃, varykštė, vorykštė. These names and their etymological aspects are discussed, the motivation for such names is described; the relation of these words to other more frequent terms for ‘rainbow’ is examined. Most of the words in question (with the exception, probably, of the term stangà, which might possibly also be of foreign origin, cf. Pol. stęga, wstęga ‘ribbon, swathe, sash’) have originated under the influence of folk etymology manifested here in various different ways. An attempt is made to demonstrate, in particular, in what way and why the forms of the analysed words have been altered, what caused their particular transformations, how the words acquired their present shapes. An attempt is also made to show the sequence of the influences of the associative “mechanisms” of folk etymology. Attention is drawn to the fact that the designation of this marvellous natural phenomenon, having innumerable mythological interpretations and related to different beliefs in various cultures of the world, has become in the Lithuanian language a real “favourite” of folk etymology.
Keywords: vaivorykštė